Declining business dynamism among our best opportunities: The role of the burden of knowledge - Thomas Åstebro; Sergej V. Braginskij; Yuheng Ding (Osaka University, Institute of Social and Economic Research (ISER), 2020)
We document that since 1997, the rate of startup formation has precipitously declined for firms operated by U.S. PhD recipients in science and engineering. These are supposedly the source of some of our best new technological and business opportunities. We link this to an increasing burden of knowledge by documentinga long-term earnings decline by founders, especially less experienced founders, greater work complexity in R&D, and more administrative work. The results suggest that established firms are better positioned to cope with the increasing burden of knowledge, in particular through the design of knowledge hierarchies, explaining why new firm entry has declined forhigh-tech, high-opportunity startups.
Keywords: 330; Wissen; Unternehmensgründung; Ingenieure; Naturwissenschaftler; Akademiker; Einkommen; USA